(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes Ghafur Ghulam’s contribution to the development of Uzbek poetry of the 20th century through the poet’s succession to literary traditions, artistic skill in the renewal of poetic images, methodological originality in the development of lyrical genres, creative influence from Uzbek folklore and the achievements of world literature. Through comparative-historical, psychological, structural-poetic, descriptive methods, it was proved that the compositional features of Ghafur Ghulam poems associated with weight, rhyme, band construction perform an important function in expressing the poetic ideas of the poet and the artistic-aesthetic characteristics of the work. It is based on the possibilities of the finger poem system, a leader in 20th-century poetry, the skillful use of the weight gills characteristic of the aruz poetry system, the characteristic lyricism characteristic of the content updates of Uzbek lyricism, the reference to poetic manifestations such as eventful lyricism.